Work Engagement : Main Factors and Supporting Factors (Study at PT. ACS Surabaya) - Arif Hidayat (Enrichment : Journal of Management, 2022)
Effective human resource management needs to pay attention to strategic aspects, which can be applied within the company so that employees contribute to achieving company excellence. What is considered strategic is work engagement, the condition of which can be shaped by many factors. So research that takes a sampling of employees of PT. ACS Surabaya finds several factors that are used as variables that have an impact on increasing employee engagement. The factor analysis that tested the discrimination index on each variable showed the correlation coefficient and the criteria determined to carry out the analysis as an influence on job involvement. The results of the analysis grouping the factors into two major parts consisting of the main factors, namely employee resources (job resources), meaningfulness (salience of job), personal employees (personal resources); and supporting factors include the work environment, co-workers support, and self-efficacy simultaneously affect work involvement. The two representative factors were able to contribute effectively to an increase in work engagement of 82.6%.